Fathoming the unfathomable - Chard, Nat; Kulper, Perry, 1953- (Pamphlet architecture, 2014)
"Kulper and Chard examine the potential of uncertainty in architecture. As this fits awkwardly with normal research methods they have each developed their own processes of study and proposal where the act of drawing is an important component in generating the content of the work. Their ways of working are contaminated by an ongoing (long distance) conversation where the exchange of work and ideas infect each other's practice and habits. The distance, mediation and time lag of their dialogue also contribute to this process. These conversations and the act of drawing rehearse the situations that are discussed by their drawings. There is a particular interest in the way evolving relationships might be discussed by their architecture, which might become spatially promiscuous in seeking out new associations. Kulper pushes the potential of both the tools and the process of traditional architectural drawing while Chard develops and builds drawing instruments particular to what he is working on"--